Influence of the gut microbiota on endometriosis: Potential role of chenodeoxycholic acid and its derivatives - Li, Yangshuo; Wang, Kaili; Ding, Jie; Sun, Shuai; Ni, Zhexin; Yu, Chaoqin (Frontiers in Pharmacology, 2022)
The gut microbiota (GM) has received extensive attention in recent years, and its key role in the establishment and maintenance of health and in the development of diseases has been confirmed. A strong correlation between the GM and the progression of endometriosis (EMS) has been observed in emerging research. Alterations in the composition and function of the GM have been described in many studies on EMS. In contrast, the GM in the environment of EMS, especially the GM metabolites, such as bile acids and short-chain fatty acids that are related to the pathogenesis of EMS, can promote disease progression. Chenodeoxycholic acid (CDCA), as one of the primary bile acids produced in the liver, is metabolized by various enzymes derived from the GM and is critically important in maintaining intestinal homeostasis and regulating lipid and carbohydrate metabolism and innate immunity. Given that the complexity of CDCA as a signalling molecule and the interaction between the GM and EMS have not been clarified, the role of the CDCA and GM in EMS should be understood from a novel perspective. However, few articles on the relationship between CDCA and EMS have been reviewed. Therefore, we review the available and possible potential links between CDCA, the GM and EMS and put forward the hypothesis that CDCA and its derivative obeticholic acid can improve the symptoms of EMS through the GM.